Menepis Wacana Jihad Masa Kini: Telaah Jihad Fi Sabilillah Dalam Islam - Moh. Khoirul Fatih (Program Studi Komunikasi dan Penyiaran Islam (KPI) Institut Agama Islam Tarbiyatut Tholabah (IAI TABAH), 2019)
This paper examines Fi Sabilillah Jihad in Islam. Jihad which is often understood as a mission to get God's blessing becomes a dynamic that often triggers the emergence of religious nuances of violence. Jihad is understood as an order to fight different groups of ideas with their groups, so that such understanding will direct religious people into the extremist and fundamental paradigms. Through this study the author tries to conclude that jihad is not an order to kill or threaten the lives of other non-Muslims. However, jihad in Islam can be interpreted as an order to fight and fight against unbelievers who insult and hostile to Islam, Allah SWT never conveyed in the Koran to kill and fight against people who were not hostile to Islam, but only ordered to fight against unbelievers who insult Islam and uphold the religion of God on earth. Specifically jihad is different from war and terrorism, jihad is an effort with a genuine sense of carrying out Allah's commands and there is no killing order in it.